Monitoring Water Quality in The Well-Water Processing System to Make Drinkable Water Based on IoT - Hendry Ponda; Uci Rahmalisa; Haris Tri Saputra; Rika Melyanti (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2024)
Indonesia is also inseparable from problems related to clean water. The city of Pekanbaru is currently experiencing rapid growth. In some big cities, the difficulty of clean water suitable for consumption is commonly felt by some residents, for example in Tuah Karya district – Pekanbaru. Moreover, this area is prone to flooding so the quality is getting worse because it smells and is cloudy. To produce clean water suitable for drinking that can be consumed by all levels of society. Water quality monitoring is also easy to do with IoT-based water quality monitoring tools. The goal of developing this prototype is to improve the healthy standard of living of the community by meeting the clean water needs of the prototype to be built. Seen from the main indicators, TDS and PH = TMS (Not Eligible) were obtained and followed by several other indicators that were still TMS. The results of the sample test showed that the water did not belong to the category of clean water and was suitable for consumption. After the water source of the drilled well is filtered using a tool made (without a manganese filter), the main indicators of TDS and pH are qualified.